2015
DOI: 10.1002/da.22462
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Availability in Mother-Child Interaction: The Effects of Maternal Depression in Remission and Additional History of Childhood Abuse

Abstract: Our data suggest that depression impacts on maternal emotional availability during remission, which might represent a trait characteristic of depression. Mothers with depression in remission and additional severe childhood abuse were particularly affected. These findings may contribute to the understanding of children's vulnerability to develop a depressive disorder themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 77 publications
(163 reference statements)
4
40
0
3
Order By: Relevance
“…Less extensive evidence also has shown that maternal depression is negatively related to prenatal bonding (Alhusen et al., ; Goecke et al., ; McFarland et al., ; Rubertsson, Pallant, Sydsjö, Haines, & Hildingsson, ). During both phases, diminished emotional availability is assumed to explain the link between depression and nonoptimal bonding (Kluczniok et al, ). Moreover, depression has the potential to reduce a woman's confidence in her new role as expectant mother (Alhusen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Less extensive evidence also has shown that maternal depression is negatively related to prenatal bonding (Alhusen et al., ; Goecke et al., ; McFarland et al., ; Rubertsson, Pallant, Sydsjö, Haines, & Hildingsson, ). During both phases, diminished emotional availability is assumed to explain the link between depression and nonoptimal bonding (Kluczniok et al, ). Moreover, depression has the potential to reduce a woman's confidence in her new role as expectant mother (Alhusen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect size was modest, confirming that the PPBS and the EDS measure different concepts. The negative association between depression and bonding may be explained by the less emotional availability depressed mothers experience [52], both during pregnancy and after birth and therefore be less able to bond well. Moreover, it is assumed that depression during pregnancy compromises a women's ability to feel confident in her new role as an expectant mother [12].…”
Section: Discussionmentioning
confidence: 99%
“…This study was performed within the framework of the Understanding and Breaking the Intergenerational Cycle of Abuse (www.ubica.de) multicentre project that investigates the effects of maternal history of abuse on mother-child interaction and child well-being. 11 This study included 114 mothers and their children aged between 5 and 12 years old (see Table 1). BPD was diagnosed in 19 mothers and MDD in remission (rMDD) was diagnosed in 71 mothers.…”
Section: Participants and Proceduresmentioning
confidence: 99%